MPS SIMULATION ON THE CORIUM MELT FLOW IN CASE OF REACTOR ACCIDENT - Tursinah, Rasito; Variastuti, Marisa; Omega, Rakotovao Lovanantenaina; Mustari, Asril Pramutadi Andi; Permana, Sidik (Website, 2023)
A simulation model has been made for molten corium in a nuclear reactor using the Moving Particle Semi-Implicit (MPS) method. By setting the value of dynamic viscosity and temperature of corium, simulations are carried out to display the pressure profile and flow velocity of the corium fluid that falls from the RPV to the plenum. In the first simulation to observe the pressure and velocity profile of the corium in the plenum, three conditions were made: the plenum was empty; the plenum was filled with corium fluid, and the plenum was filled with debris. The second simulation was carried out to determine the relationship between the time required for corium to reach the plenum for variations in corium viscosity and temperature values. The simulation results show that the increase in corium viscosity will be proportional to the length of time it takes to reach the plenum. In contrast to the effect of temperature where the increase in corium temperature will be the smaller the time required.